Superionic conduction of silver in homogeneous chalcogenide glasses. Issue 3 (17th December 2015) - Marple, M.; Kaseman, D. C.; Kim, S.; Sen, S.
Abstract : Homogeneous Ag–Ga–Ge selenide glasses display fast silver ion conduction at ambient temperature. Abstract : Fast ion conducting glasses are of key interest for their potential applications in energy conversion/storage, memory, display and sensor technologies. However, the best contenders in this class of materials suffer from the lack of thermodynamic stability against phase separation, devitrification and moisture attack. We report the finding of novel off-stoichiometric glass-forming chalcogenide alloys in the system Ag–Ga–Ge–Se characterized by modified random networks that overcome these debilitating problems and at the same time display superionic silver conduction at ambient temperature. Combined application of multi-nuclear magnetic resonance, Raman and electrochemical impedance spectroscopy provides a fundamental understanding of the potential energy landscape for silver ion transport in these materials.